Exploring prototype methodology in land information system development: design and evaluation of an application - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
Land management in the modern era requires efficient and responsive information systems to facilitate timely and effective decision-making. However, the development of land rights information systems is often faced with complex challenges such as diverse user needs, legal uncertainty, and administrative complexity. This research uses a prototype approach to develop a land rights information system application. The first stage involved data collection to identify user needs and the state of existing information systems. The second stage involved developing an application prototype based on the identified user needs. The third stage is prototype testing with end users to gather feedback. The final stage is user acceptance analysis to evaluate the application's performance, functionality, and usability. The result of this research is a prototype of a land rights information system application that has been improved and refined based on user feedback. User acceptance analysis showed a good level of satisfaction and acceptance of the prototype, with the prototype method helping to reduce development time and costs and providing a faster response to changing user needs.